Distribution Network Expansion Analysis Using Branching Optical Distribution Point (ODP) and Fiber Optic Attenuation (FO) Methods - Husain Husain; Engelbertus Mite; Raisul Azhar; Lilik Widyawati; Apriani Apriani (Jurnal Bumigora Information Technology (BITe), 2023)
Background : Data access using copper is considered slower than Fiber Optic access networks, which encourages many customers who switch to Fiber Optic. Objective : This study aims to analyze the installation of Fiber Optic networks using Optic System Software in new areas and analyze attenuation in Fiber Optic networks using Link power budget. Method : The method used in this study is PPDIOO : Prepare, Plan, Design, Implement, Operate, and Optimize. Results : The Optical Power Meter (OPM) simulation on the new ODP using Opti System produces a value of receiving power (Pr) -19.48 dBm (as a sample) and for the calculation results using the Power Link Budget (PLB) the total value of receiving Power (Pr) -20.40 dBm while Measurement results using Optical Power Meter (OPM) (Pr) -19.89 dBm (as a sample). Conclusion : The results of measurements and measurements have similarities, namely if the distance between the Optical Distribution Cabinet (ODC) and Optical Distribution Point (ODP) is greater, the greater the value of the receiving power or attenuation.